Chimpanzees (Pan troglodytes) strategically manipulate their environment to deny conspecifics access to food - Kaufhold, Stephan P.; Sánchez-Amaro, Alejandro; Tan, Jingzhi; Fernandez-Navarro, Sofia; Atencia, Rebeca; Rossano, Federico (Scientific reports, 2024)
Humans modify their environment to grant or prevent others’ access to valuable resources, for example by using locks. We tested whether sanctuary-living chimpanzees (N = 10) would flexibly modify their environment to either allow or deny a dominant conspecific access to a shared food source by giving them the option to change a food reward’s pathway prior to releasing it. The food could end up in one of two locations: one was accessible to both the subject and a dominant conspecific, the other one was only accessible to the subject. We further manipulated the extent of inhibitory control needed for modifying the pathway by varying the subjects’ starting position. Our subjects reoriented the pathway competitively to monopolize food but changed the pathway less often in trials with high inhibitory demands. We further show how inhibitory task demands in a social context influence chimpanzees’ future planning. Our results show that chimpanzees will strategically manipulate their environment to maximize their own and deny a dominant conspecific access to food.